Mode of delivery in chorioamnionitis: impact on neonatal and maternal outcomes - Vanessa R. Kay; Isabella Liang; Jennifer Twiss; Michelle Morais (BMC, 2024)
Abstract Background The impact of mode of delivery in chorioamnionitis on neonatal outcomes is unclear. This retrospective cohort study compares the rate of early onset neonatal sepsis between vaginal delivery and cesarean section. Methods Singleton pregnancies at greater than 24 + 0 weeks gestation with live birth and clinically-diagnosed chorioamnionitis from January 1, 2019 to December 31, 2021 were included. Cases with multiple gestations, terminations or histological chorioamnionitis alone were excluded. Rates of early onset neonatal sepsis, select secondary neonatal outcomes and a composite outcome of maternal infectious morbidity were compared using propensity score weighting. Subgroup analysis was done by indication for cesarean section. Results After chart review, 378 cases were included with 197 delivering vaginally and 181 delivering via cesarean section. The groups differed on age, parity, hypertension, renal disease, gestational age, corticosteroid use, magnesium sulfate use, presence of meconium and percentage meeting Gibbs criteria before propensity score weighting. Rate of early onset neonatal sepsis was greater in the cesarean section group (13.8% versus 3.1%, adjusted risk difference 8.3% [3.5-13.1], p < 0.001). Secondary neonatal outcomes were similar between groups. When compared by indication, the rate of early onset neonatal sepsis was greater in the cesarean section for abnormal fetal surveillance group compared to vaginal delivery but not in the cesarean section for other reasons group. Adjusted rates of secondary neonatal outcomes did not differ between groups. The rate of maternal infectious morbidity was greater with cesarean section. (13.8% versus 1.5% [adjusted risk difference 13.0% [7.1-18.9], p < 0.0001). No other difference in maternal secondary outcomes was identified. Conclusions The rate of early onset neonatal sepsis was highest in the cesarean section group, particularly in those with abnormal fetal surveillance. Fetuses affected by or vulnerable to sepsis likely have a greater need for cesarean section.